Formação Docente: o texto literário como mediadora nas discussões reflexivas em ATPC - Oliveira, Sheila Aparecida Pereira de (2018)
This exploratory study aims to analyze a training offered in ATPC, using literary art as a mediator. The proposal of formation, inspired by the psychogenetic theory of HENRI WALLON that postulates the integration between the affectivity, cognition and movement sets, introduced small narratives of Eduardo Galeano to dialogue with texts of Paulo Freire. The context where the research was carried out was a Primary School and Secondary School, therefore with specialist teachers. The deponents' speech revealed that the use of different languages, in this case, literary art, positively affected the participants of the ATPC and mobilized them to use these resources with their students